Total Synthesis of (+)-Rubriflordilactone A - Goh, Shermin S (Angew Chem Int Ed Engl, 2015)
Two enantioselective total syntheses of the nortriterpenoid natural product rubriflordilactone A are described, which use palladium- or cobalt-catalyzed cyclizations to form the CDE rings, and converge on a late-stage synthetic intermediate. These key processes are set up through the convergent coupling of a common diyne component with appropriate AB-ring aldehydes, a strategy that sets the stage for the synthetic exploration of other members of this family of natural products.